Kesalahan Terjemahan Dalam Teks Alih Bahasa Inggris-Indonesia Serial Original Netflix: The Queen’s Gambit - Putri Sutaji, Tirta Ningtyas Alifia (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study aims to identify translation errors from English to Indonesian in the Netflix Original Series. The data in this study were taken from the subtitles of the Netflix Original Series entitled "The Queen's Gambit" which consists of 7 episodes. The reading and writing method was the data collection method chosen in this study, while in analyzing the data, the Error Analysis method was used using the List of Translation Errors from NAATI as a reference. The results of the study found 56 translation errors classified into 7 categories, namely Distortion with 12 errors, Unjustified Omission with 21 errors, Inappropriate Register with 10 errors, Unidiomatic Expression with 6 errors, Error of Grammar with 1 error, Error of Spelling with 3 errors, and Error of Punctuiation with 3 errors. Where Unjustified Omission which is a translation error by removing elements from the source language to the target language is the most common error.